Learning of Genre Text Descriptive Writing Through Implementing the Number Head Together Strategy Towards Students’ at Junior High School 2 Tondano - Wimsje R. Palar (Journal of International Conference Proceedings (JICP), 2020)
This study aims, 1) to describe the application of the Number Head Together (NHT) strategy in learning to write the descriptive text genre to seventh grade students of Junior High School 2 Tondano (SMP), Minahasa Regency, North Sulawesi Province. 2) to describe the application of the Number Head Together Strategy in order to maximize the ability of grade VII students of Junior high school 2 Tondano in writing descriptive text genre. The method used in this research is descriptive method. The subjects of this study were 30 students of class VII of Junior high school 2 Tondano. This research was conducted at Junior high school 2 Tondano. The techniques used in collecting this data are tests and observations. The indicator used in this study is the completeness of learning both individually and in groups, namely at least 75%. The results showed that (1) the application of the Number Head Together Strategy could maximize the ability of the seventh grade students of Junior high school 2 Tondano in writing descriptive texts because the class average score achieved was 83.3%, (2) The maximum score of the students in writing descriptive texts was related to Students' attention and activities are classified as' good '(above 50%) and (10%) are classified as' lacking'. The steps for the Number Head Together Strategy in learning to write descriptive text are: (1) Introduction (2) Core Activities (3) Closing: a) Giving descriptive text writing tests to students, b) Informing students of the results that have been achieved, c) Providing follow-up exercises in the form of writing descriptive text to students that are not optimal.